(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Women are vital members of society who contribute significantly to the well- being of their families and society at large. Objective: The objective of this paper was to study the invisible barriers as a challenge in the career advancement for women in the hospitality industry and to seek the female worker’s views on work place grievances within the hotel industry. Methodology: Quantitative research design was used to understand the challenges faced by female employees working in the hotel. The items in the questionnaire included working women issues related key parameters like sexual and mental harassment, promotion issues, family care issues, discrimination based on gender, workplace discrimination and prejudices, work life balance issues etc. A questionnaire-based survey of female (60) hotel workers in Kolkata was done. The data was collected using the personal contact approach. Results: The majority age group that participated in the study was under 21 to 29 years. About 78.3 % respondent’s organization does not provide with childcare facility, though 73.3 % respondent’s organization do provide with adequate maternity leave. Around 60 % of the respondent’s promotion took longer than those of male colleagues in the similar rank, which focus light on gender inequality. About 75 % women experienced biasness in their place of work based on gender. Gender discrimination and biasness are still existential in the industry. The rate of work satisfaction, stood at 43.3 %. Conclusion: The result explains that there are areas that are slowly changing for the betterment of women, there is still few barriers and challenges that makes it difficult for a female employee in a hotel industry. Women representation at the senior level is also proportionately very low compared to men. Conflict between work and family is a real juggling act for women which may at times lead her to make a choice between career and home.